Dual-mode chaotic oscillator: Applications for art and music - Tantrakunphaisan, Udomsit; Klomkarn, Kitdakorn; Sooraksa, Pitikhate (My University, 2018)
This paper presents new dual chaotic attractors. The dual-mode chaotic system is comprised inductorless Chua's circuit and a chaotify Wien bridge chaotic s oscillator. The objective of the proposed circuit is to teach undergraduate students. The proposed circuit is simple and can be rapidly constructed in the laboratory. Two potential applications are provided for arts and music.
Keywords: Chaotic oscilator; Engineering Education; Music Engineering